Numerical investigation into the effect of surface wettability in pool boiling heat transfer with a stochastic-automata model - Marcel, Christian Pablo (2017)
Surface wettability is a key property in boiling heat transfer that influences heat-removal mechanisms and/or change their relative relevance. An automata model for pool boiling heat transfer is provided with rules to simulate heat transfer considering the influence of the contact angle. Free bubbles are modeled as a population of virtual spheres that change their geometric properties with simple stochastic rules. The model is validated against published experimental pool boiling data, showing excellent agreement with the boiling curve, as well as with the activation of nucleation sites, in a statistical sense. The sensitivity of the model parameters is studied to assess their influence and relevance. The model also provides information about the behavior of other near-wall relevant quantities, such as the interfacial area density and bubble detachment frequency. The computing time is around two orders of magnitude lower than the required by continuum methods to simulate pool boiling.